PENGARUH KEPUASAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWANPT. BANK BNI (PERSERO) TBK CABANG AMBON - Tousalwa, Carla (Arthavidya Jurnal Ilmiah Ekonomi, 2016)
Study aimed to clarify whether the variable jobsatisfaction and work motivation significantly influence employeeperformance, as well as to determine which variables are thedominant influence between the two variables Job Satisfactionand Work Motivation on the performance of employees at PT.Bank BNI (Persero) Tbk Ambon Branch. Samples were takenusing purposive sampling method is to direct all employeeschoose as many as 50 people. The results showed that jobsatisfaction and work motivation have a significant effect on theperformance of employees of PT. Bank BNI (Persero) Tbk AmbonBranch. Variable job satisfaction and work motivation improvethe performance of employees of PT. Bank BNI (Persero) TbkAmbon Branch. The correlation between job satisfaction andwork motivation and performance of employees of PT. Bank BNI(Persero) Tbk Ambon Branch is very strong.Keywords: Job satisfaction, motivation and performance ofemployees